Incidence and clinical significance of 6q deletions in B cell chronic lymphocytic leukemia - Stilgenbauer, Stephan; Bullinger, Lars; Benner, Axel; Wildenberger, Kathrin; Bentz, Martin; Döhner, Konstanze; Ho, Anthony Dick; Lichter, Peter; Döhner, Hartmut (Leukemia, 1999)
Deletions affecting the long arm of chromosome 6 (6q) are among the most commonly observed chromosomal aberrations in lymphoid malignancies and have been identified as adverse prognostic factor in subsets of tumors. Whereas at least two regions of minimal deletion have been established, one in 6q21-q23 and another in 6q25-q27, no tumor suppressor gene that might be involved in the pathogenesis of lymphoid malignancies has been so far identified from these segments. For B cell chronic lymphocytic leukemia (B-CLL) conflicting data have been reported regarding the incidence and prognostic significance of 6q deletions. In the current study we have used two YAC clones mapping to deletion regions in bands 6q21 and 6q27 as probes for fluorescence in situ hybridization (FISH) in a large series of B-CLL cases to analyze the incidence, localization and clinical significance of 6q aberrations. Among 285 patients with B-CLL studied we identified 21 cases (7%) with 6q deletions. All deletions were found with the probe mapping to 6q21 while the 6q27 region was deleted only in a third of these cases. Analysis of the clinical characteristics and laboratory parameters showed that the patients with 6q deletions had higher white blood cell counts and more extensive lymphadenopathy. However, the overall survival and the treatment-free intervals were similar in the two groups. We conclude that deletions in 6q21 occur in 7% of B-CLL and identify a subgroup of patients characterized by a larger tumor mass but no inferior outcome.